Makna Teologis Busana Liturgis dalam Gereja - Herman Punda Panda (SOLA GRATIA: Jurnal Teologi Biblika dan Praktika, 2022)
Abstract: De facto liturgical vestments are an integral part of the liturgical ministry in the churches. However, there are differences in understanding and interpreting the history which has been developed after the apostles' time. In terms of the use of liturgical clothing, each church has a unique perspective and practice, although there are a number of elements in common. Through the study of the literature on liturgical vestments, the author discusses the development of these garments, both the various types that have existed and those that are currently used in churches. The author analyzes past events related to the origin, development, and theological understanding of the subject to understand the peculiarities of how they are viewed today. In addition, the author also makes a comparison of the use of liturgical clothing from different ecclesiastical contexts. This research shows that the different attitudes towards liturgical vestments are closely related to the different understandings of the priesthood. Churches which maintain the doctrine of in persona Christi in ordained ministers tend to maintain the majesty of the liturgical vestments of the medieval heritage. On the other hand, churches that do not accept this doctrine use minimalistic liturgical clothing and even consider it optional. In this case, Luther's adiaphora principle is quite influential in the freedom to use or not to use liturgical clothing. Abstrak: Busana liturgis, de facto, merupakan bagian integral dari pelayanan liturgi dalam gereja-gereja. Walaupun demikian, terdapat perbedaan dalam memahami dan menafsirkan sejarah yang berkembang sesudah era para rasul. Dalam hal penggunaan busana liturgis, masing-masing gereja memiliki cara pandang dan praktek yang khas, walaupun terdapat pula sejumlah unsur yang sama. Melalui studi pustaka, penulis mengangkat perkembangan penggunaan busana liturgis, baik ragam jenis pakaian yang pernah ada maupun yang saat ini digunakan di gereja-gereja. Penulis menganalisis peristiwa masa lalu yang berkaitan dengan asal, perkembangan, dan makna teologis busana liturgis untuk memahami kekhasan pandangan masa kini tentang pakaian tersebut. Selain itu, penulis juga membuat perbandingan penggunaan busana liturgis dari konteks gerejawi yang berbeda-beda. Penelitian ini menunjukkan bahwa perbedaan sikap gereja-gereja terhadap busana liturgis berkaitan erat dengan pemahaman yang berbeda atas imamat. Gereja-gereja yang mempertahankan doktrin in persona Christi dalam diri pelayan tertahbis cenderung mempertahankan pula keagungan busana liturgis warisan abad pertengahan. Sebaliknya gereja-gereja yang tidak menerima doktrin tersebut menggunakan busana liturgis secara minimalis bahkan menganggapnya tidak wajib. Dalam hal ini prinsip adiaphora dari Luther cukup berpengaruh dalam kebebasan menggunakan atau pun tidak menggunakan busana liturgis.